Analytical-field investigation of the effect of elastic modulus parameter of the cement treated base (CTB) according to FAA manual on the airfield concrete block pavement (ACBP) performance - Amir Ebrahim Daheshpour; Parham Hayati (Case Studies in Construction Materials)
The demand for high-performance concrete block pavements (CBPs) in airport aprons has grown due to their influence on service quality and Foreign Object Debris (FOD) prevention. CBPs offer notable advantages in maintenance and tensile strength. This study evaluates the load-bearing capacity and deflection behavior of airfield concrete block pavement (ACBP) under Boeing 747–8 F loads, integrating field measurements and ABAQUS software analysis. Constructed with a compacted subgrade, sub-base, crushed aggregate base, cement-treated base (CTB), and herringbone-patterned concrete blocks, the pavement structure was tested with the Plate Loading Test (PLT) under varied conditions. Deflections at different points were recorded using LVDT sensors, and 3D simulations focused on evaluating the performance of the CTB layer and its influence on the behavior of airfield block pavement. The findings highlight the significant role of CTB tensile strain in determining pavement performance under heavy loads. Optimizing the elastic modulus of CTB layers can effectively minimize deflection and ensure compliance with FAA standards. Notably, deflection at the pavement corner was 50 % greater than at the center under 740.4 kPa pressure, underscoring the importance of design improvements to support repeated loadings. A CTB with the minimum FAA-compliant elastic modulus is recommended to enhance load-bearing performance.